Non-independent speed control for dual-PMSM drives fed by a single three-leg VSI - Jurifa Mat Lazi; Zulkifilie Ibrahim; Md Hairul Nizam Talib (Institute of Advanced Engineering and Science, 2020)
The objective of this article is to analyze the performances of non-independent speed control of dual-pmsm (permanent magnet synchronize motor) drives by a single three-leg voltage source inverter (VSI) using control of mean and differential torque technique. In general, there are two types of control strategies for dual-motor drives. One is master-slave technique and another one is mean control technique. For mean control technique, this study chooses mean and differential approach for the motors parameters and using average value for the voltage space vector. The advantages of dual-motor drives fed by a single inverter topology are, it can decrease the size and cost compared to the dual-motor drives which used by individual inverter, either in industrial or in traction applications. However, by using a single three-phase inverter, the topology only restricted for the same operating conditions which are at the same speed, same parameters and same direction. The dual-motors are dependent (non-independent) on the other motor. It is can only be tested on different load operation. The analysis is focuses on speed and load variation for dual-PMSM drives considering the forward and reverse operations of the motor. This simulation model is modelled using MATLAB-Simulink.